“Expecting the Unexpected:” Nurses' Response and Preparedness of Terrorism-Related Disaster Events in Quetta City, Pakistan - Khilji, Fazal ur Rehman; Raziq, Abdul; Shoaib, Maryam; Baloch, Nosheen Sikander; Raza, Shanaz; Iqbal, Zaffar; Ishaq, Rabia; Haider, Sajjad; Iqbal, Qaiser; Ahmad, Nafees; Saleem, Fahad (Frontiers in Public Health, 2021)
Background: In addition to the psychiatric and societal misery, terrorism places an exceptional burden while delivering healthcare services. Accordingly, a responsive and well prepared healthcare system ensures effective management of terrorism-related events. Within this context, with a strong historic grounding in addressing situations of societal crisis nurses are well placed in contributing to the global arena of humanitarian policy and social research. Therefore, assessing their response and preparedness is vital in effective management of a terrorism-related disaster. For that very reason, we aimed to evaluate nurses’ preparedness and response towards terrorism-related disaster events in Quetta city, Pakistan. Methods: A qualitative design was adopted to explore nurses’ response and preparedness of terrorism-related disaster events. By using a semi-structured interview guide through the phenomenology-based approach, in-depth, face-to-face interviews were conducted. Nurses practicing at the Trauma Center of Sandeman Provincial Hospital (SPH), Quetta, were approached for the study. All interviews were audio-taped, transcribed verbatim, and were then analyzed for thematic contents by the standard content analysis framework. Results: Fifteen nurses were interviewed and thematic content analysis revealed five themes. All nurses have experienced, responded to, and managed terrorism-related disaster events. They were prepared both professionally and psychologically in dealing with a terrorism-related disaster. Among limitations, space and workforce were highlighted by almost all the respondents. Lack of disaster-related curricula, absence of a protocol, recurrence of the disaster, and hostile behavior of victim’s attendants during an emergency were highlighted as a key barrier towards terrorism-related disaster management. Conclusion: The skills and expertise needed to address a terrorism-related disaster are well understood by the nurses but are lacking for various reasons. In addition to the review and adaption of the nursing curriculum specifically for terrorism-related disaster management, collaboration and dialogue between various stakeholders is required to efficiently manage terrorism-related disaster events.